2006
DOI: 10.1074/jbc.m608147200
|View full text |Cite
|
Sign up to set email alerts
|

Post-meiotic Shifts in HSPA2/HSP70.2 Chaperone Activity during Mouse Spermatogenesis

Abstract: HSPA2 (formerly HSP70.2) is a testis-specific member of the HSP70 family known to play a critical role in the completion of meiosis during male germ cell differentiation. Although abundantly present in post-meiotic cells, its function during spermiogenesis remained obscure. Here, using a global proteomic approach to identify genome-organizing proteins in condensing spermatids, we discovered an unexpected role for HSPA2, which acquires new functions and becomes tightly associated with major spermatid DNA-packag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 19 publications
8
85
0
Order By: Relevance
“…Third, a phosphoproteome analysis of mutant testes revealed that HSPA2 (Hsp70.2) may be a target of PPP1CC (Henderson et al 2010). HSPA2 protein decorates the synaptonemal complex of pachytene spermatocytes, and is also present in a cloud of puncta over the chromatin (Govin et al 2006, Henderson et al 2010; this latter pattern is missing from Ppp1cc mutant spermatocytes, supporting the intriguing possibility that dephosphorylated HSPA2 performs a second function, different from that identified by the null mutation and related to conditioning of the germ cell chromatin in preparation for the major morphological changes the cells are about to embark upon. Furthermore, HSPA2 is highly expressed by spermatocytes and spermatids in the human testes (Son et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Third, a phosphoproteome analysis of mutant testes revealed that HSPA2 (Hsp70.2) may be a target of PPP1CC (Henderson et al 2010). HSPA2 protein decorates the synaptonemal complex of pachytene spermatocytes, and is also present in a cloud of puncta over the chromatin (Govin et al 2006, Henderson et al 2010; this latter pattern is missing from Ppp1cc mutant spermatocytes, supporting the intriguing possibility that dephosphorylated HSPA2 performs a second function, different from that identified by the null mutation and related to conditioning of the germ cell chromatin in preparation for the major morphological changes the cells are about to embark upon. Furthermore, HSPA2 is highly expressed by spermatocytes and spermatids in the human testes (Son et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The testis HSP70-null male mice are infertile due to meiotic arrest in spermatocytes (17,37,39), and HSP70 may be essential in the later stages of spermatogenesis that involve SIP and SSTK. To our knowledge, SIP represents the first demonstration of a germ cell-specific cochaperone for a protein kinase that requires the HSP90 machinery for activation, and in addition to Cdc37, is only the second cochaperone identified that plays a role in protein kinase maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Our work revealed new functions for HSPA2 during post-meiotic phases, when it becomes specifically associated with transition proteins [Govin et al 2006a]. This heat shock protein appeared, therefore, as the first identified chaperone for the non-histone testis-specific DNA-packaging proteins.…”
Section: Identification and Functional Investigations Of Selected Facmentioning
confidence: 90%
“…Altogether, these data suggest that the action of Brdt on hyperacetylated chromatin is crucial for the subsequent stages of genome reorganizations which could cooperate with tH2B/H2AL2 nucleosomes to mediate histone replacement by TPs. Additionally, we could show that in elongating spermatids, these TPs are chaperoned by HSPA2 [Govin et al 2006a], a factor which has been shown to also play a critical meiotic role by mediating the desynapsis of synaptonemal complexes [Eddy 1998]. It is also tempting to propose that HSPA2 also contributes to the exchange of histones by TPs and uses its ATPase domain to facilitate nucleosome disassembly and the incorporation of TPs.…”
Section: Identification and Functional Investigations Of Selected Facmentioning
confidence: 99%